Associations between sociodemographic and level of knowledge, attitudes and practices towards COVID-19 among nursing students of University Malaysia Sabah, Malaysia - Abdul Rahman Ramdzan; Danish Shazrein Binti Kaslan; Mohd Nurman Bin Aman Setia; Don Harris Bin Sundang; Hetrice Hunsoi; Rachel Chin Zin Vun; Tan Ker Xin; Mohana A/P Saran; Zulkhairul Naim Sidek Ahmad (DiscoverSys Inc., 2022)
Background: The novel coronavirus disease (COVID-19) emerged in Wuhan, China, in December 2019. Since then, it has spread to 215 countries, and 42 million people around the globe are affected. The knowledge, attitudes, and practices (KAP) toward COVID-19 play a role in determining the acceptance of behavioral change measures from health authorities to suppress this pandemic status. The KAP on COVID-19 is also important among university students during the COVID-19 pandemic to mitigate the outbreak of COVID-19. Hence, this study aimed to determine the level of knowledge, attitudes and practices towards COVID-19 and its association with sociodemographic factors among nursing students of Universiti Malaysia Sabah. Methods: A cross-sectional, questionnaire-based study was conducted among the Year 1, Year 2 and Year 3 nursing students. The questionnaire consists of four parts: 1) demographics, which surveys participants’ sociodemographic information; 2) knowledge about COVID-19; 3) attitude towards COVID-19; and 4) practices relevant to COVID-19. Statistical Package for Social Science (SPSS) version 26.0 was used for data entry and analysis. Result: A total of 113 Nursing Students participated in the study. More than half of the respondents have good general knowledge and practices of COVID-19. However, only one in three respondents have positive attitudes towards COVID-19. Older age was associated with good knowledge about COVID-19 (p=0.02). Female (P=0.02) and high household income (P=0.02) has a better attitude towards COVID-19. However, no significant association between sociodemographic and practices towards COVID-19. Conclusion: Most of the respondents demonstrate a good level of knowledge and practices towards COVID-19 but not for attitudes. Sociodemographic characteristics such as younger, male respondents and those with lower-income families have inadequate knowledge and practices towards COVID-19. Hence, health education programs such as campaigns need to be conducted to increase the knowledge and encourage adequate preventive practice towards COVID-19 should be targeted towards this group.